MASSIVE SULFIDE DEPOSITS OF ENSIMATIC ISLAND ARCS OF KAZAKHSTAN ON THE EXAMPLE OF ABYZ DEPOSIT - Aleksey K. Mazurov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2020)
The relevance of the studyis caused by the need to highlight new conditions for formation of massive sulfide mineralization (Au-Cu-Pb-Ag) in late-stage ensimatic island arcs. This study shown that the prospects of ensimatic island arcs are not fully exhausted. The work aim is to study the petrological, mineralogical and geochemical features of the rocks and ore composition to clarify criteria in forecasting and searching for massive sulfide mineralization in ensimatic island- arc geological formations. Research methods included studying the composition of rocks and ores using classical mineralogical, petrographic, and mineralographic analyzes and scanning electron microscopy. The chemical composition was determined using silicate analysis. Chemical analysis data were recalculated using the T. Bart oxygen method to determine the influx and removal of chemical elements. The results. The massive sulfide deposits of Kazakhstan were mainly formed in the island-arc geodynamic condition. The island-arc paleosystems are subdivided into ensimatic and ensialic. The formation of the Rudny Altai polymetal belt is associated with ensialic island arcs. The Abyz deposit is associated with the formation of the late stage evolution of ensimatic island arc. The island-arc base was laid on the oceanic crust and is predominantly represented by sedimentary rocks, such as volcanomictic and polymictic sandstones, conglomerates, and siltstones. The main initial rocks of deposit were changed by intense hydrothermal-metasomatic processes, which was reflected in propylization and berezitization. Thirteen ore bodies were formed within the deposit as a result of metasomatic processes. Morphology of ore bodies is complex with lenticular, lenticular-stratum forms. The main minerals of massive sulfide ores are chalcopyrite, pyrite, sphalerite, galena, fahlore, tellurides (altaite, rucklidgeite) and gold inclusions. The silver content in gold is up to 12,5%.